The Model Of Product Quality, Promotion, Price, And Purchase Decisions - Imaningsih, Erna S. (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
The development of increasingly complex consumer needs and increasingly sharp market competition causes HONDA must be able to compete to show the benefits of its products and grab the attention of the consumers, one way to do it is to create a new product class SUV Medium namely HONDA H-RV. Consumers who will take the decision in choosing HONDA H-RV will consider various things in buying. Considerations are influenced by product quality, price, and promotion. Analytical techniques using validity test, Realibility test, multiple linear regression, t test, F test with SPSS 23.0 tool. based on the results of statistical calculations with linear regression analysis can be shown by the regression equation Y = 1,956 + 0,462X1 + 0,239X2 + 0,256X3 + e from regression equation known that product quality, price, and promotion have positive influence to purchasing decision. The result of calculation coefficient of determination equal to 0,673, it shows that product quality, price, and promotion are able to explain purchase decision equal to 67,3%. While the remaining 32.7% is explained by other variables that are not observed. Based on the result of data analysis, it can be concluded that there is positive influence of product quality, price, and promotion to decision of purchase of HONDA H-RV and have strong correlation level, it means if product quality, price, and promotion is increased it will result in high purchase decision